EXPERIMENTAL ANALYSIS OF MESH ELEMENTS GLULAM DOME (Collection of scientific works «Modern structures of metal and wood», 2023)
To study the stress-strain state of the mesh dome model with the diameter 4 m, the series of glulam rods were prepared for the central compression test. The tests were carried out in the  laboratory  of  the  Department  of  Metal,  Wooden  and  Plastic  Structures.  The  stresses  at  the distinguished points of the elements were determined through the deformations using the resistance strain  sensors.  The  feature  of  prismatic  samples  was  the  presence  of  stress  concentrators  in  the support zones in the form of the holes for the location of universal connectors [3]. The significant sizes of the model made it possible to minimize the influence of the scaling factor on the obtained results. The general conclusion of the study should be considered high bearing capacity of the tested samples. The destruction of the samples took place in the support zone due to the crushing of the wood. The next tasks of the research will be the optimization of the elements sizes and testing of the dome model. The cross-section of the elements, in addition to providing the load-bearing capacity, is  affected by  the  need  to  obtain  certain  thermotechnical  characteristics  of  the  enclosure,  i.e.  the elements of the dome must have the dimensions that allow placing a layer of effective insulation in their plane. A separate task is the selection of the roof, which can be considered exclusively as a part  of  the permanent  load  on  the  supporting  system,  or  as  a  continuous  shell  that  unfastens  the frame.